Adenovirus viremia after in vivo T-cell depleted allo-transplant in adults: low lymphocyte counts are associated with uncontrolled viremia and fatal outcomes. Issue 2 (28th January 2022) - Chaekal, Ok-Kyong; Soave, Rosemary; Chen, Zhengming; Shore, Tsiporah; Mayer, Sebastian; Phillips, Adrienne; Mei Hsu, Jing; Gomez-Arteaga, Alexandra; Rennert, Hanna; Drelick, Alex; Orfali, Nina; Walsh, Thomas J.; et al.
Abstract: The incidence of adenovirus viremia and the role of screening in preventing adenovirus disease in adult transplant recipients are not well defined. Between January 2017 and May 2020, 262 allogeneic transplants were performed using in vivo T-cell depletion. Adenovirus viremia was found in 59 patients for a cumulative incidence of 10% by one hundred days and 23% (95% CI 20–26%) by one year. There was a higher incidence of viremia associated with cord blood transplant ( p = .04). No other patient, donor or transplant characteristics were identified that predicted for viremia. In 47 patients (80%), viremia remained well below 200, 000 copies/mL and resolved. Twelve patients developed high level viremia. Treatment with antivirals and in some cases adoptive cell therapy, was often ineffective and only two survived. Low lymphocyte count at initial detection of adenovirus viremia was the best predictor of uncontrolled disease.